Pole-mounted Gulf service station sign - Rohm and Haas Company (1956)
General view of a Plexiglas pole-mounted Gulf service station sign manufactured by the Rohm and Haas Company. The Rohm and Haas Company was founded in 1907 in Esslingen, Germany through the partnership of German chemist Otto Röhm and German businessman Otto Haas. In 1933, Röhm's experiments with the polymerization of methyl methacrylate led to the creation of a clear, solid plastic sheet, which he trademarked Plexiglas. During World War II, the demand for Plexiglas, which both Allied and Axis forces used for submarine periscopes and aircraft windshields, canopies, and gun turrets, helped transform Rohm and Haas into a major chemical firm.
Keywords: Rohm and Haas Company; Corporations; Plexiglas; Plastics industry and trade; Gulf Oil Corporation; Branding (Marketing)